Factors affecting the volatility of stock price in Malaysia / Laila Aliza M. Tajudeen - M. Tajudeen, Laila Aliza (Faculty of Business and Management, 2018)
This research paper studies the relationship between stock price of Kuala Lumpur Composite Index (KLCI) with three economic determinants which are Exchange Rate (ER), Money Supply (MS) and Real Interest Rate (RIR) from year 1987 to 2016 on a yearly basis with a total of 30 observations. However, instead of in emerging markets such as Malaysia most of the studies are carried out in developed countries and large economic nations. Thus, this study aims to extend the existing studies to include the impact of several economics determinants namely Exchange Rate (ER), Money Supply (MS) and Real Interest Rate(RIR) on stock price (KLCI). This paper employed Multiple Linear Regression to examine the statistical relationship and to test the hypotheses. The results had portrays that independent variables which are Exchange Rate (ER) and Money Supply (MS) are significant relationship towards stock price (KLCI). Meanwhile, the results indicated that there is insignificant relationship between Real Interest Rate (RIR) with stock price (KLCI).